A frequency-domain grinding force model-based approach to evaluate the dynamic performance of high-speed grinding machine tools. Issue 1 (2nd January 2016) - Guo, Miaoxian; Li, Beizhi
ABSTRACT: This article provides an integrated approach to evaluate grinding machine's dynamic performance in speed range by examining both the manufacturing process and the machine tool. This approach considers the dynamic grinding force as a starting point. The dynamic change of the cutting depth in the grinding process is studied first. Then, based on the dynamic model of grinding process developed in previous studies, the dynamic forces of the manufacturing process are predicted. By analyzing the grinding force model in the frequency-domain and the frequency response function, the root mean square values of the machine vibration are calculated. The evaluation works by comparing the variation and trend of the vibration level. The proposed evaluation method is then applied to a physical grinding machine. The dynamic performance obtained from the experiment matches the predicted trend in the models. In addition, this method can be used to inspect and optimize the design of the machine's spindle system. For the grinding process that requires a high dynamic performance, this method also provides reference for the speed selection within all speed range.